Ethnic Background and Overweight among 5-Year-Old Children: The "Be Active, Eat Right" Study. (10th October 2013) - Veldhuis, Lydian; van Dooremaal, Mara; Kroeze, Willemieke; Renders, Carry M.; HiraSing, Remy A.; Raat, Hein
Abstract : Introduction . This study investigates the association between ethnic background and overweight (obesity included) among 5 year olds. Methods . We used baseline data from 5 year olds (n = 7801 ) and their parents collected for the "Be active, eat right" study. A child was considered to be of non-Dutch ethnic background when at least one of the parents was born abroad. Odds ratios (ORs) were adjusted for sociodemographic characteristics. Results . Compared to children of Dutch ethnic background, for children with a Moroccan ethnic background the OR for being overweight (obesity included) was 2.27 (95% CI 1.48–3.47), for Turkish children the OR was 3.63 (95% confidence interval (CI) 2.46–5.35), for Antillean children the OR was 1.97 (95% CI 1.01–3.86), and for Surinamese children the OR was 0.47 (95% CI 0.20–1.06). Addition of parental overweight decreased the ORs for Moroccan and Turkish children by 10.2% and 12.5%, and addition of watching TV and having breakfast by the child decreased the ORs by 7.9% and 12.2%. Conclusion . Already at a young age, children of Moroccan and Turkish ethnic background are at increased risk for being overweight compared to Dutch children. Parental overweight, watching TV, and not having breakfast by the child are contributing factors in this association.